THE POWER OF LISTENING: EXPLORING EFFECTIVE TEACHING BY CHRISTIAN RELIGIOUS EDUCATION TEACHERS - Elisabeth Sitepu; Johanes Waldes Hasugian; Sharon Salsalina G Munthe; Javerson Simamora (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the role of listening in the pedagogical practices of Christian Religious Education (CRE) teachers with an emphasis on the function and strategy of listening as a holistic and relational approach. Through observation of narrative literature on various educational literature, this study identified four main functions of listening, namely: building trust relationships, upholding equality, being a means of assessment, and as a relational pedagogical tool. In addition, four main strategies were found that can be applied by CRE teachers, namely: listening in three stages (pre, during, and post), metacognitive and critical strategy, a holistic approach, and listening attentively. This study also revealed the contradiction between the function of listening as an evaluative versus relational tool, as well as research related to the quantitative influence of listening on student learning outcomes. These results indicate the importance of listening as a form of professional ethics, an expression of love, and a means to explore spiritual meaning in the relationship between teachers and students. This study recommends strengthening CRE teacher training in developing listening competencies as an integral part of transformative teaching.